"With my sword in my hand" : the politics of race and sex in the fiction of Zora Neale Hurston - Schmidt, Rita Terezinha (1983)
Even though the upsurge of interest in Hurston’s works during the seventies was followed by concrete scholarly attempts to rescue her fiction from anonymity, the recently available criticism has not addressed, with thoroughness and comprehensiveness, those aspects that constitute the core of her narratives: the exploration of male/female power relations and the depiction of the female experience of oppression, particularly the black woman’s, within the insular folk community. Hurston’s fiction brings into being a new way of appropriating the black reality by probing the question of female oppression at a time when the political content of sexual power relations was not yet fully recognized, especially in the black community. Thus, this study proposed a feminist reading of her fiction, a reading that focuses on the ways in which Hurstons portrays the patriarchal relations of dominance and dependency in the sphere of intimacy; and on the ways in which her texts raise equations between sexual oppression and the assertion of manhood, between woman’s subordination and the enslavement of a race and, between patriarchal oppression and white capitalist oppression. Assuming that literally works cannot be disengaged from the social process and that the vitality and authenticity of the world they depict cannot be understood apart the dialectical interchange between the subjective and objective, this reading articulates an adjacent three-fold purpose: 1 – to insert Hurston into the context of the Harlem Renaissance so as to understand the relationship of the writer to her time, as well as to establish the ideological wellsprings of her fiction; 2- to reinvent the links between her texts, particularly the short stories, history and personal reality so as to establish the determinants of race, class and gender on Hurston’s literary self-expression; 3- to liberate new meanings from certain narrative strategies, in particular, characterization, authorial manipulation and point of view, and to examine the emotional rapport of author/female characters, which will inevitably lead to the question of identifications. At this point, her works will be seen in terms of and ideological practice in which Hurston herself, as a subject, is inserted. The black feminism that emerges out of a synthesis of literally praxis and subjective reality intimates, ultimately, a level of political coherence between her fiction’s racial expression and its thematic concern with female oppression.